Potential missed opportunities to prevent ischaemic stroke: prospective multicentre cohort study of atrial fibrillation-associated ischaemic stroke and TIA. Issue 7 (24th July 2019) - Wilson, Duncan; Ambler, Gareth; Shakeshaft, Clare; Banerjee, Gargi; Charidimou, Andreas; Seiffge, David; White, Mark; Cohen, Hannah; Yousry, Tarek; Salman, Rustam; Lip, Gregory Y H; Muir, Keith; et al.
Abstract : Objective: We report on: (1) the proportion of patients with known atrial fibrillation (AF); and (2) demographic, clinical or radiological differences between patients with known AF (and not treated) and patients with newly diagnosed AF, in a cohort of patients who presented with ischaemic stroke or transient ischaemic attack (TIA) not previously treated with anticoagulation. Design: We reviewed cross-sectional baseline demographic and clinical data from a prospective observational cohort study, (CROMIS-2). Setting: Patients were recruited from 79 hospital stroke centres throughout the UK and one centre in the Netherlands. Participants: Patients were eligible if they were adults who presented with ischaemic stroke or TIA and AF and had not been previously treated with oral anticoagulation. Main outcome measures: Proportion of patients with known AF before index ischaemic stroke or TIA from a cohort of patients who have not been previously treated with oral anticoagulation. Secondary analysis includes the comparison of CHA2 DS2 -VASc and HAS-BLED scores and other demographics and risk factors between those with newly diagnosed AF and those with previously known AF. Results: Of 1470 patients included in the analysis (mean age 76 years (SD 10)), 622 (42%) were female; 999 (68%) patients had newly diagnosed AF and 471 (32%) patients had known AF. Of the 471 patients with known AF, 68% had a strong indication for anticoagulation and 89% should have been considered for anticoagulation based upon CHA2 DS2 -VASc score. Patients with known AF were more likely to have a prior history of dementia (4% vs 2%, p=0.02) and had higher HAS-BLED scores (median 3 vs 2). CHA2 DS2 -VASc, other risk factors and demographics were similar. Conclusions: About 1/3 of patients who present with stroke and have AF who have not been treated with oral anticoagulation have previously known AF. Of these patients, at least 68% were not adequately treated with oral anticoagulation. Trial registration number: NCT02513316 .